Cloning and analysis of promoter of Paralichthys olivaceus Follistatin gene - LIU Qing-hua; TAN Xun-gang; XU Yong-li; ZHANG Pei-jun; ZHANG Yu-qing (浙江大学学报. 农业与生命科学版)
In order to study the tissue expression character of Follistatin gene in marine fish, the promoter of Paralichthys olivaceus Follistatin gene was isolated by PCR, and the sequence was analyzed; the function of Follistatin gene on the development of muscle was studied by RT-PCR and microinjection. The results indicated that the promoter had many transcription factor binding sites such as USF, E47, MyoD and NF-Y, et al; in Paralichthys olivaceus adult tissues, Follistatin expressed in body kidney, intestine, heart, head kidney and spleen, while did not express in muscle and liver; microinjection revealed that Follistatin gene played a role in the early development of muscle.